2009
DOI: 10.1186/1476-9255-6-34
|View full text |Cite
|
Sign up to set email alerts
|

Gadolinium decreases inflammation related to myocardial ischemia and reperfusion injury

Abstract: BackgroundThe lanthanide cation, gadolinium (GdCl3) protects the myocardium against infarction following ischemia and reperfusion. Neutrophils and macrophages are the main leukocytes responsible for infarct expansion after reperfusion. GdCl3 interferes with macrophage and neutrophil function in the liver by decreasing macrophage secretion of inflammatory cytokines and neutrophil infiltration. We hypothesized that GdCl3 protects against ischemia and reperfusion injury by decreasing inflammation. We determined t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
2
5
0
1
Order By: Relevance
“…In this study, we found that lowdose GdCl 3 dramatically inhibited AA-induced Ca 2+ overload and elevated resting [Ca 2+ ] i in A/R NRVMs ( Figure 3B-E). We also demonstrated that low-dose GdCl 3 significantly ameliorates I/R-induced cytochrome c release in vivo ( Figure 5H) and in vitro ( Figure 3A) and inhibits cell apoptosis via regulation of Previous studies have demonstrated that pathophysiological responses triggered after reperfusion include the release of activation factors and free radicals, which activate phospholipase A 2 and increase AA release [24] . The accumulated AA in the myocardium may play an important role in post-I/R injury because a time-dependent degradation of membrane phospholipids associated with an increase in membrane permeability was observed in the ischemic myocardium [17,38] .…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…In this study, we found that lowdose GdCl 3 dramatically inhibited AA-induced Ca 2+ overload and elevated resting [Ca 2+ ] i in A/R NRVMs ( Figure 3B-E). We also demonstrated that low-dose GdCl 3 significantly ameliorates I/R-induced cytochrome c release in vivo ( Figure 5H) and in vitro ( Figure 3A) and inhibits cell apoptosis via regulation of Previous studies have demonstrated that pathophysiological responses triggered after reperfusion include the release of activation factors and free radicals, which activate phospholipase A 2 and increase AA release [24] . The accumulated AA in the myocardium may play an important role in post-I/R injury because a time-dependent degradation of membrane phospholipids associated with an increase in membrane permeability was observed in the ischemic myocardium [17,38] .…”
Section: Discussionsupporting
confidence: 56%
“…GdCl 3 (10 mg/kg) has been demonstrated to exert a protective potential in I/R-induced brain injury and hepatic injury and to protect the myocardium against I/R-induced inflammation via the reduction of circulating monocytes and neutrophils and the infiltration of leukocytes. This dose also attenuated myocardial stunning when administered prior to the onset of ischemia or during ischemia, but it did not enhance the contractile function of normal myocardium [21][22][23][24] . However, the precise mechanism(s) underlying the effect of GdCl 3 are not known.…”
Section: Introductionmentioning
confidence: 91%
“…These results indicated a critical role of M1 microglia/macrophages in inducing the necroptosis of astrocytes after SCI. Considering that GdCl 3 also affects neutrophils [ 38 ], which are abundant in the injury epicenter after SCI, and that iNOS can also be expressed by neutrophils [ 39 ]. The beneficial effects of GdCl 3 treatment may also be contributed by the inhibition of neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…Recent experiments demonstrate that inflammation plays a major role in ischemia-reperfusion injury (IRI) [1][2][3], and anti-inflammatory treatment provides protection against myocardial IRI [4,5]. It is generally believed that production and release of proinflammatory cytokines can be regulated by specifically augmenting cholinergic signaling via the efferent vagus nerve and the α7 subunit-containing nicotinic acetylcholine receptor (α7nAChR) [6].…”
Section: Introductionmentioning
confidence: 99%